An active disturbance rejection synchronous control strategy based on cross compensation for stepper motor XY platform. (March 2023) - Chen, Guangda; Xue, Ruonan; Song, Chao; Liu, Dejun; Ren, Letian; Cheng, Yanming
In view of the system uncertainty factors and bilateral drive synchronization problems of XY platform driven by stepping motor, on the basis of the mathematical model of single axis servo system, in order to improve traceability and disturbance rejection in X, Y direction, a double loop structure with PID controller as speed loop and active disturbance rejection as position loop is proposed to solve the contradiction between rapidity and overshoot, moreover, an ESO performance analysis method is proposed, and the parameter tuning rules of ADRC is summarized. On this basis, a deviation self-coupling compensation control strategy is proposed to solve the problem of bilateral drive synchronization in axis X direction, and the mechanism and parameter adjusting method of the compensator are studied. The comparative experiment between ADRC+PID+deviation self-coupling compensation and PID+PID+deviation self-coupling compensation, the comparative experiment between ADRC+PID+deviation self-coupling compensation and ADRC+PID are conducted, respectively. Finally, the experiment of synthetic trajectory of X and Y is carried out, the simulation and experimental results demonstrate that the response time of the control strategy proposed in this paper is 0.5 s, which is 0.2 s faster than PID's, and the disturbance recovery time is 50% of PID control. Therefore, the proposed ADRC+PID+deviation self-coupling compensation control strategy can not only effectively improve the tracking performance of the XY platform system, but also enhance the robustness of the system.